The role of the military in democratization processes: The cases of Egypt and Tunisia - Küçük, Ömer Naim. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Why do some militaries allow institutionalization of democratic reforms, whereas others disrupt them? By process-tracing the critical processes in Tunisia and Egypt, this research examines why the Egyptian military intervened in the democratization process and ended democratic reforms, whereas Tunisia military avoided acts that would undermine the democratization. The main argument is that if the transitional government threatens the material corporate interests of the military, the military may intervene in politics to disrupt democratic reforms. The author argues that one of the important keys to understanding the military's impact on the outcome of the democratization process is to analyze changing trends in military's corporate material interest, which are conceptualized in three variables: Military budget, the privileges of the military-owned enterprises, and the disbursement of the foreign military aid. The study finds that if the transitional government fails to increase military budget, the military is more likely to disrupt the democratization. Conversely, the appeasement of the military by increasing military budget is a useful strategy in reducing he mili ar ’ willi g e end democratization. The study also finds that if the transitional government threatens the privileges of the military-owned enterprises, the military is more likely to involve in politics to disrupt democratic reforms. Finally, the transitional government's bilateral relations with the donor countries have an impact on the outcome of the democratization process. Findings indicate that if the military is dependent on military aid, it is more likely to disrupt democratization if such transition threatens to disrupt the flow of aid.
Keywords: Militarism -- Egypt.; Militarism -- Tunisia.; Democracy -- Egypt.; Democracy -- Tunisia.